2010
DOI: 10.1111/j.1600-0501.2010.01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Flap vs. “flapless” surgical approach at immediate implants: a histomorphometric study in dogs

Abstract: "Flapless" implant placement into extraction sockets did not result in the prevention of alveolar bone resorption and did not affect the dimensional changes of the alveolar process following tooth extraction when compared with the usual placement of implants raising mucoperiosteal flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 18 publications
6
73
1
4
Order By: Relevance
“…On the contrary, some other studies have found no significant differences in bone level changes between the two surgical protocols. Caneva et al (2010) observed comparable buccal bone dimensions in both groups in an animal study at 4 months.…”
Section: Flap Versus Flapless Approachmentioning
confidence: 68%
See 2 more Smart Citations
“…On the contrary, some other studies have found no significant differences in bone level changes between the two surgical protocols. Caneva et al (2010) observed comparable buccal bone dimensions in both groups in an animal study at 4 months.…”
Section: Flap Versus Flapless Approachmentioning
confidence: 68%
“…In order to further elucidate this question, Caneva et al (2010) performed a similar investigation in a canine model. At 4 months of healing, a buccal plate reduction of 1.7mm in experimental sites and 1.5mm in control sites was seen.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…El rango de estos cambios de dimensión tiene una variación interindividual; expresándose en el biotipo gingival fino una mayor predisposición a presentar reabsorción y recesión que los pacientes con fenotipo grueso y escasamente festoneado. La literatura expresa que la zona de mayor riesgo de reabsorción es el centro vestibular, resultando en menores cambios dimensionales a nivel proximal (3,5) . Se identificó un espesor óseo vestibular menor o igual a 1mm como factor crítico asociado con la reabsorción vestibular; los fenotipos de pared delgada visualizan pronunciadas pérdidas verticales con una medida de 7.5 mm en comparación con fenotipos de pared gruesa con pérdidas de 1.1 mm (6,7) .…”
Section: Introductionunclassified
“…The range of these dimensional changes has an interindividual variation: the thin periodontal biotype has a higher predisposition to resorption and recession than the thick biotype with low scalloping. The literature points to the vestibular center as the area with greatest resorption risk, resulting in lower dimensional changes in the proximal area (3,5) . We identified a vestibular bone thickness lower than or equal to 1 mm as a critical factor associated with vestibular resorption; the thin wall phenotypes displayed marked vertical losses, measuring 7.5 mm compared with thick wall phenotypes with losses of 1.1 mm (6.7) .…”
Section: Workhop 1 -Ideal Time For Implant Placement: Immediate Earmentioning
confidence: 99%